Abnormal thermal expansion properties of cubic NaZn13-type La(Fe, Al)13 compounds1. Issue 8 (28th February 2015) - Li, Wen; Huang, Rongjin; Wang, Wei; Zhao, Yuqiang; Li, Shaopeng; Huang, Chuanjun; Li, Laifeng
<x xml:space="preserve">Abstract</x> Remarkable NTE properties as well as near ZTE behavior are observed in the LaFe13−xAlx (x = 1.8–2.7) compounds.